Faktor Determinan Profitabilitas Unit Usaha Syariah Di Indonesia Tahun 2018-2022 - Muliana, Muliana; Destiana, Yolanda; Cipta, Hendra (JYRS: Journal of Youth Research and Studies, 2025)
This study aims to find out how simultaneously Non-Performing Financing (NPF), Operating Costs, Operating Income (BOPO) and Financing to Deposit Ratio (FDR) have a significant effect on the Profitability of Sharia Business Units in Indonesia in 2018-2022. The variables of this study consist of independent variables and dependent variables. The independent variables are Non Performing Financing (NPF), Operating Expenses, Operating Income (BOPO) and Financing to Deposit Ratio (FDR) and the dependent variable Return On Asset (ROA). This type of research is quantitative descriptive using multiple linear regression tests. This approach is carried out by deductive thinking to find hypotheses. The data collection technique of this study is documentation. The data analysis techniques used are descriptive statistical analysis, classical assumption tests, hypothesis tests using the SPPS software version 26 program tools. The results of this study show that the NPF independent variable has no effect on ROA based on the tcount > ttable = -2.141 > 2.056, with a significant value = 0.042 < 0.05. The BOPO variable had no effect on ROA based on the tcount < ttable = -1.465 < 2.056 with a significant value = 0.155 > 0.05. The FDR variable has an effect on ROA based on the tcount < ttable = 3.339 > 2.056, with a significant value = 0.003 < 0.05. NPF, BOPO and FDR simultaneously have a significant effect on the Profitability of Sharia Business Units in Indonesia in 2018-2022. Based on the value of Fcount > Ftable = 5.336 > 2.29, with a significant value = 0.005 > 0.05.